The Effects of a Carbohydrate Hydrogel System for the Delivery of Bicarbonate Mini-Tablets on Acid–Base Buffering and Gastrointestinal Symptoms in Resting Well-trained Male Cyclists - Lewis A. Gough; S. Andy Sparks (Sports Medicine - Open, 2024)
Abstract Background A new commercially available sodium bicarbonate (SB) supplement claims to limit gastrointestinal (GI) discomfort and increase extracellular buffering capacity. To date, no available data exists to substantiate such claims. Therefore, the aim of this study was to measure blood acid–base balance and GI discomfort responses following the ingestion of SB using the novel “Bicarb System” (M-SB). Twelve well-trained male cyclists completed this randomised crossover designed study. Maximal oxygen consumption was determined in visit one, whilst during visits two and three participants ingested 0.3 g∙kg−1 BM SB using M-SB (Maurten, Sweden) or vegetarian capsules (C-SB) in a randomised order. Finger prick capillary blood samples were measured every 30 min for pH, bicarbonate (HCO3 −), and electrolytes (potassium, chloride, calcium, and sodium), for 300 min. Visual analogue scales (VAS) were used to assess GI symptoms using the same time intervals. Results Peak HCO3 − was 0.95 mmol∙L−1 greater following M-SB (p = 0.023, g = 0.61), with time to peak HCO3 − achieved 38.2 min earlier (117 ± 37 vs. 156 ± 36 min; p = 0.026, r = 0.67) and remained elevated for longer (p = 0.043, g = 0.51). No differences were observed for any electrolytes between the conditions. Aggregated GI discomfort was reduced by 79 AU following M-SB (p < 0.001, g = 1.11), with M-SB reducing stomach cramps, bowel urgency, diarrhoea, belching, and stomach-ache compared to C-SB. Conclusions This is the first study to report that M-SB can increase buffering capacity and reduce GI discomfort. This presents a major potential benefit for athletes considering SB as an ergogenic supplement as GI discomfort is almost eliminated. Future research should determine if M-SB is performance enhancing.